Silicon and germanium waveguides for silicon photonics - Zhang, Heng (2017)
With the rapid development of silicon photonics, significant amount of work have been done on this topic to facilitate the speed of development on silicon photonics, including active and passive devices for a range of applications, such as deposited waveguides, modulators and drivers, multiplexers, mid-infrared silicon photonics and so on. Most of them play an important role in solving the interconnection problems, a large number of researches that are applied in some new fields has been carried out in recent years, including sensors applications and the applications about mass market photonics. The waveguides as a passive device did not attract a lot of attentions in the past years. A lot of efforts that are mainly focused on the lasers [1] and detectors [2] [3] or other active devices. Most of the researchers neglected or did not spend a lot of time on the researches about the passive components, such as lenses [4], or waveguides [5] [6]. Although the active devices have significant impacts and effects on the development of silicon photonics, the effects of passive devices and components cannot be neglected, because a lot of devices cannot function well without them. For example, in the mid-infrared field, some elementary components such as splitters, resonators, waveguides and couplers, which are indispensable and essential components for the integrated optical devices to function and work well. Among all of these passive components, waveguide plays a key role in many fields. This report discusses the properties and applications about silicon, germanium and other materials related to the waveguides. In addition, it detailedly analyses the properties of some strip waveguides such as Silicon-on-Insulator waveguide and Germanium-on-Silicon waveguide, and discusses how they function and work under different conditions. Simulation and design of these waveguides are performed in order to obtain the best structure and the optimized properties especially for the applications in the mid-infrared region, which are very promising for the future study. These designs aim to achieve the minimum propagation loss value under the conditions that only single modes transmit through the waveguide. Key words: mid-infrared, strip waveguides